Adolescent with Rhabdomyolysis due to Undiagnosed Hypothyroidism - Raquel Farias Moeller; Nassim Zecavati; Rosa Sherafat-Kazemzadeh; Shoshana Aleinikoff; Wolfgang Rennert (Case Reports in Pediatrics)
Exercise-induced rhabdomyolysis has been described in military recruits, trained athletes and daily runners. Statin use, quail ingestion, infection by Epstein-Barr virus (EBV), and hypothyroidism, though rare, are risk factors for the development of rhabdomyolysis. We describe the case of a 15-year-old female who presented with myalgias, weakness, and pigmenturia following marching band practice. Laboratory tests confirmed an elevated creatine kinase (CK) level as well as a profound hypothyroid state. Muscle biopsy revealed severe muscle necrosis and myositis. Treatment with levothyroxine resulted in obtaining an euthyroid state and regain of muscle strength as well as decrease in CK levels. Although rare, hypothyroidism should be considered as a potential cause of rhabdomyolysis in pediatric patients undergoing a myopathy workup.